High levels of zinc (Zn) as a protective factor and negatively correlated with IgM anti PGL-1 levels among household contact with multibacillary leprosy patients - Adeline Santoso; Luh Made Mas Rusyanti; Ketut Kwartantaya Winaya (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Background: Close contacts may develop subclinical leprosy with no symptoms but with M. leprae in their blood. Zinc is said to help in the prevention of M. leprosy infection. This study aimed to determine the correlation between zinc (Zn) serum levels and IgM anti PGL-1 levels in household contacts of multibacillary type leprosy patients. Methods: This study is cross-sectional and involves 48 leprosy subjects (33 multibacillary leprosy household contact and 15 non-contact subjects). Subjects were selected based on the inclusion and exclusion criteria. Zinc and IgM anti PGL-1 levels were derived from venous blood examined with ELISA. Results: This study showed the mean serum zinc level of the contact groups of 60.88 ± 15.92 μg/dl and the non-contact group of 90.00 ± 7.61 μg / dl (p <0.001; CI 95%: 20.38 - 37.85). The median (interquartile range) serum levels of IgM anti PGL-1 in the contact groups was 613.00 (40 - 1433) u/ml and the non-contact groups was 99.00 (14 - 695) u/ml (p = 0.001; 95% CI: 154.162 – 610.116). The correlation analysis between serum zinc levels and IgM anti PGL-1 serum levels r= 0.644 (p<0.05). A high serum zinc level is a protective factor against high IgM anti PGL-1 levels in household contact with leprosy (PR: 0.47; 95% CI: 0.20-1.09). Conclusion: Zinc levels negatively correlate with IgM anti PGL-1 levels in subjects with household contact with multibacillary type leprosy. A high serum zinc level protects against high IgM anti PGL-1 levels.